Sosok Dewa Indra Menurut Beberapa Karya Sastra Jawa Kuna - Sugeng Riyanto (Balai Arkeologi Yogyakarta, 1994)
Literature (philology) is one of the important textual data. Apart from containing historical information, it also contains information about the king, the government, life in the palace, and the life of the people. It also contains the information about iconography of both gods and goddesses in Hinduism. This means with certain treatment of literary works, the life aspects of Old Javanese people can be understood. In this regard, this short article is intended to describe the figure of Dewa Indra, based on a study of several Old Javanese literary works. Dewa Indra known as one of the Loka Pala gods as inscribed on the Civa Temple, Prambanan. It is hoped that a picture from the other side of Dewa Indra can be revealed, which in turn can also reveal the tendency of the poets to present the figure of Dewa Indra.